Impact of antibody-mediated rejection detected on one-year protocol biopsies on long-term kidney allograft survival - Galina Severova; Vlatko Karanfilovski; Lada Trajceska; Irena Rambabova-Bushljetik; Pavlina Dzekova-Vidimliski; Igor G. Nikolov; Nikola Gjorgjievski; Gordana Petrushevska; Slavica Kostadinova-Kunovska; Goce Spasovski; Ninoslav Ivanovski (Frontiers in Medicine, 2026)
Introduction Kidney transplantation undoubtedly remains the best way of treatment for end-stage chronic kidney disease. Enormous success has been achieved in improving short-term graft survival, but long-term graft survival has presented a great challenge, especially from an immunological perspective. This study aimed to evaluate the impact of antibody-mediated rejection (ABMR) detected on one-year protocol graft biopsies in kidney transplant recipients with stable graft function on 10-year death-censored graft survival and overall patient survival. Material and methods Fifty adult kidney transplant recipients with stable graft function underwent a one-year protocol graft biopsy. According to the Banff 2013 classification, recipients were classified into ABMR and non-ABMR groups and followed until graft loss, death, or completion of the 10-year post-transplant follow-up. All of them were with low to moderate immunological risk, with no preformed Donor Specific Antibodies (DSA). The treatment consists of induction therapy, Anti-Thymocyte Globulin (ATG) or Basiliximab, and standard triple immunosuppressive therapy: steroids, Mycophenolate mofetil (MMF), and calcineurin inhibitors. Tissue samples were evaluated according to the BANFF 2013 classification by one pathologist. According to findings from graft biopsies, patients were divided into two groups: ABMR and non-ABMR. They were followed from the time of transplantation until graft loss, death, or completion of the 10-year post-transplant follow-up, whichever occurred first. We compared the two groups for demographic and other factors that could influence the immunological profile of the patient. Also, we evaluated the death-censored graft survival and overall survival of the patients. Results Fifteen recipients (30%) had ABMR lesions on the one-year protocol biopsy, while 35 (70%) had no evidence of ABMR. Baseline demographic characteristics, immunological risk factors, immunosuppressive therapy, and graft function did not differ significantly between the groups. Recipients with ABMR had significantly inferior 10-year death-censored graft survival (log-rank p = 0.049). In univariate Cox regression, ABMR was associated with an increased risk of graft loss (HR 2.79, 95% CI 1.01–7.70; p = 0.047), while logistic regression demonstrated higher odds of graft failure (OR 3.86, 95% CI 1.07–13.94; p = 0.049). Overall patient survival did not differ significantly between the groups. Conclusion In this cohort, ABMR detected on one-year protocol graft biopsies was associated with inferior 10-year death-censored graft survival in kidney transplant recipients with stable graft function. These findings suggest that one-year protocol biopsies may provide useful prognostic information for identifying recipients at increased risk of long-term graft loss. However, given the small sample size, limited number of graft failure events, and observational study design, these findings should be interpreted as an association rather than evidence of a definitive prognostic effect and require confirmation in larger, preferably multicenter cohorts.